Vaccination With Recombinant Filamentous fd Phages Against Parasite Infection Requires TLR9 Expression - Gomes-Neto, João F.; Sartorius, Rossella; Canto, Fábio B.; Almeida, Thamyres S.; Dias, André A.; Barbosa, Carlos-Henrique D.; Melo, Guilherme A.; Oliveira, Ana Carolina; Aguiar, Pedro-Henrique N.; Machado, Carlos R.; de Matos Guedes, Herbert L.; Santiago, Marcelo F.; et al. (Frontiers in Immunology, 2018)
Recombinant filamentous fd bacteriophages (rfd) expressing antigenic peptides were shown to induce cell-mediated immune responses in the absence of added adjuvant, being a promising delivery system for vaccination. Here, we tested the capacity of rfd phages to protect against infection with the human protozoan Trypanosoma cruzi, the etiologic agent of Chagas Disease. For this, C57BL/6 (B6) and Tlr9-/- mice were vaccinated with rfd phages expressing the OVA257-264 peptide or the T. cruzi immunodominant peptides PA8 and TSKB20, and challenged with either the T. cruzi Y-OVA or Y strain, respectively. We found that vaccination with rfd phages induces anti-PA8 and anti-TSKB20 IgG production, expansion of Ag-specific IFN-γ- TNF-α- and Granzyme B (GzB)-producing CD8+ T cells, as well as in vivo Ag-specific cytotoxic responses. Moreover, the fd-TSKB20 vaccine was able to protect against mortality induced by a high-dose inoculum of the parasite. Although vaccination with rfd phages successfully reduced both parasitemia and parasite load in the myocardium of WT B6 mice, Tlr9-/- animals were not protected against infection. Thus, our data extend previous studies, demonstrating that rfd phages induce Ag-specific IgG and CD8+ T cell-mediated responses and confer protection against an important human parasite infection, through a TLR9-dependent mechanism.